The Complete Plastomes of Five Hemiparasitic Plants (Osyris wightiana, Pyrularia edulis, Santalum album, Viscum liquidambaricolum, and V. ovalifolium): Comparative and Evolutionary Analyses Within Santalales - Guo, Xiaorong; Liu, Changkun; Zhang, Guangfei; Su, Wenhua; Landis, Jacob B.; Zhang, Xu; Wang, Hengchang; Ji, Yunheng (Frontiers in Genetics, 2020)
Most species of Santalales (the sandalwood order) are hemiparasites, including both facultative and obligate hemiparasites. Despite its rich diversity, only a small fraction of the species in the sandalwood order have sequenced plastomes. The evolution of parasitism–associated plastome reduction in Santalales remains under-studied. Here, we report the complete plastomes of three facultative hemiparasites (Pyrularia edulis, Cervantesiaceae; Osyris wightiana and Santalum album, Santalaceae), and two obligate hemiparasites (Viscum liquidambaricolum and V. ovalifolium, Viscaceae). Coupled with publicly available data, we investigated the dynamics of plastome degradation in Santalales hemiparasites. Our results indicate that these hemiparasites can be characterized by various degrees of plastome downsizing, structural rearrangement, and gene loss. The loss or pseudogenization of ndh genes was commonly observed in Santalales hemiparasites, which may be correlated to the lifestyle shift from photoautotroph to hemiparasitism. However, the obligate hemiparasites did not exhibit a consistently higher level of gene loss or pseudogenization compared to facultative hemiparasites, which suggests that the degree of plastome reduction is not correlated with the trophic level facultative or obligate hemiparasitism. Instead, closely related taxa tend to possess highly similar plastome size, structure, and gene content. This implies the parasitism-associated plastome degradation in Santalales may evolve in a lineage-specific manner.